Tallas, proporción de sexos y reproducción de Myliobatis califomica y M. longirostris (Pisces: Myliobatidae) en Baja California Sur, México - Villavicencio Garayzar, Carlos J (Universidad de Costa Rica, 1996)
The commercial catch in Almejas Bay, Mexico, was monitored from August 1990 through December. Sizes in male and female M. califomica were 37-86 and 30-128 cm DW, respectively; in M. longirostris they respectively were 31-59 and 31-88 cm. M. californica give birth, ovulate and mate during spring-summer. In both species, males begin rnaturity around 50 cm DW.